Makna dan Nilai Moral Ritual Adat Hela Keta Perkawinan Suku Oepikan Desa As Manulea Kecamatan Sasitamean Kabupaten Malaka - Dionesia Seravia Mea; Yustina Sako; Emeliana Tai; Agustinus Seran (Lembaga Pengembangan Kinerja Dosen, 2024)
The Meaning and Message of Moral Values ​​in the Hela Keta Traditional Ritual According to the Marriage of the Oepikan Tribe, As Manulea Village, Sasitamean District, Malaka Regency